2007
DOI: 10.3354/ab00014
|View full text |Cite
|
Sign up to set email alerts
|

Clicking for calamari: toothed whales can echolocate squid Loligo pealeii

Abstract: Squid play an important role in biomass turnover in marine ecosystems and constitute a food source for ~90% of all echolocating toothed whale species. Nonetheless, it has been hypothesized that the soft bodies of squid provide echoes too weak to be detected by toothed whale biosonars, and that only the few hard parts of the squid body may generate significant backscatter. We measured the acoustic backscatter from the common squid Loligo pealeii for signals similar to toothed whale echolocation clicks using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 42 publications
(69 reference statements)
1
51
0
Order By: Relevance
“…Sperm whale echolocation clicks have been studied in detail by several authors, who demonstrated that they are adapted to locate medium-sized squids, among other prey (Madsen et al, 2002(Madsen et al, , 2007Mohl et al, 2003;André et al, 2007). The most common pulsed sound emissions heard during sperm whale deep dives are 'usual clicks'.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm whale echolocation clicks have been studied in detail by several authors, who demonstrated that they are adapted to locate medium-sized squids, among other prey (Madsen et al, 2002(Madsen et al, , 2007Mohl et al, 2003;André et al, 2007). The most common pulsed sound emissions heard during sperm whale deep dives are 'usual clicks'.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the acoustic scattering by cuttlefish is expected to fluctuate in proportion with changes in the overall density of cuttlebone. Madsen et al (2007) reported that the muscular mantle and fins of the common squid are the dominant scatterers, and that the hard parts-such as beak, eyes and pen-contribute little to the TS of squid, at least for frequencies representative of the clicks of most teutophageous toothed whales. This suggests that the acoustic interference of the muscular mantle, fins and cuttlebone in freely swimming cuttlefish are complexly generated based on frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about beaked whale ecology, particularly their dive patterns (Baird et al, , 2008Hobson and Martin, 1996;Hooker and Baird, 1999;Tyack et al, 2006) and acoustic behaviors Frantzis et al, 2002;Johnson et al, 2004Johnson et al, , 2006Johnson et al, , 2007Jones et al, 2008; 0025-326X/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.marpolbul.2011.01.003 Madsen et al, 2005Madsen et al, , 2007Pavan et al, 2009;Zimmer et al, 2005Zimmer and Pavan, 2008) has been enhanced by recent studies.…”
Section: Introductionmentioning
confidence: 99%